Keats : the Myth of the Hero. - Van Ghent, Dorothy Bendon (Princeton legacy library., 2014)
Focusing in a new and thoroughgoing way on Keats's widely discussed interest in Greek myth, Professor Van Ghent finds the underlying coherence in both his poetry and his letters to be archetypes of the hero and his double""--Pervasive myths of creation and generation reflected in his poetics of desire. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of